Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Ask your questions and receive precise answers from experienced professionals across different disciplines. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

[tex] \rm \int_{0}^ \infty \frac{ \sqrt[ \scriptsize\phi]{x} \tan^{- 1} (x)}{(1 + {x}^{ \phi} {)}^{2} } {}^{} {} \: dx\\ [/tex]​

Sagot :

With ϕ ≈ 1.61803 the golden ratio, we have 1/ϕ = ϕ - 1, so that

[tex]I = \displaystyle \int_0^\infty \frac{\sqrt[\phi]{x} \tan^{-1}(x)}{(1+x^\phi)^2} \, dx = \int_0^\infty \frac{x^{\phi-1} \tan^{-1}(x)}{x (1+x^\phi)^2} \, dx[/tex]

Replace [tex]x \to x^{\frac1\phi} = x^{\phi-1}[/tex] :

[tex]I = \displaystyle \frac1\phi \int_0^\infty \frac{\tan^{-1}(x^{\phi-1})}{(1+x)^2} \, dx[/tex]

Split the integral at x = 1. For the integral over [1, ∞), substitute [tex]x \to \frac1x[/tex] :

[tex]\displaystyle \int_1^\infty \frac{\tan^{-1}(x^{\phi-1})}{(1+x)^2} \, dx = \int_0^1 \frac{\tan^{-1}(x^{1-\phi})}{\left(1+\frac1x\right)^2} \frac{dx}{x^2} = \int_0^1 \frac{\pi2 - \tan^{-1}(x^{\phi-1})}{(1+x)^2} \, dx[/tex]

The integrals involving tan⁻¹ disappear, and we're left with

[tex]I = \displaystyle \frac\pi{2\phi} \int_0^1 \frac{dx}{(1+x)^2} = \boxed{\frac\pi{4\phi}}[/tex]